2018
DOI: 10.28998/2525-4200.2018v3n1.694-709
|View full text |Cite
|
Sign up to set email alerts
|

Assistência à Mulher no Pré-Natal, Parto e Nascimento: Contribuições da Rede Cegonha

Abstract: Objetivo: Analisar na literatura, a assistência prestada à mulher no prénatal, parto e nascimento após a implantação da Rede Cegonha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
5
0
6
Order By: Relevance
“…In a study carried out in Goiás, Brazil, which showed results that concern the data of this research, all participants reached the minimum number of six prenatal consultations, as recommended by the Ministry of Health, however, despite the increased coverage of prenatal care was observed among the primiparous mothers of this study, the quality of care was not satisfactory among these pregnant women monitored at the service (6) .…”
Section: Discussionmentioning
confidence: 43%
“…In a study carried out in Goiás, Brazil, which showed results that concern the data of this research, all participants reached the minimum number of six prenatal consultations, as recommended by the Ministry of Health, however, despite the increased coverage of prenatal care was observed among the primiparous mothers of this study, the quality of care was not satisfactory among these pregnant women monitored at the service (6) .…”
Section: Discussionmentioning
confidence: 43%
“…The published studies have shown that after the implementation of the Stork Network, there have been some advances, such as the encouragement of natural childbirth and increased engagement of obstetric nursing work to provide pregnant women with humanized assistance. 21 A reduction in the infant mortality rate and maternal mortality was also found. 22 However, some parameters need to be improved, such as providing orientation about breastfeeding, repeated tests for syphilis, HIV, and Hepatitis B, and improving the linkage between pregnant women and the reference maternity.…”
Section: Introductionmentioning
confidence: 81%
“…19,20 The Stork Network has four strategic components: I -Prenatal; II -Childbirth and birth; III -Puerperium; IV -Comprehensive attention to children's health; Logistic system; Transport and regulation. 21,22 The Stork Network is a relatively recent initiative and, for this reason, few studies are found in the literature investigating its impact. The published studies have shown that after the implementation of the Stork Network, there have been some advances, such as the encouragement of natural childbirth and increased engagement of obstetric nursing work to provide pregnant women with humanized assistance.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, é imprescindível que tais profissionais estejam atualizados não só em conhecimentos técnicos e práticos, mas também em fluxogramas de serviços, em suas respectivas áreas de atuações. 5,10 Outro desafio a ser enfrentado é o transporte seguro e rápido da mulher gestante ou da criança em situações de emergência. Para isso, um fácil contato e uma quantidade suficiente de ambulâncias são imprescindíveis para a sua concretização.…”
Section: Conclusãounclassified
“…A capacitação dos profissionais e a sistematização da rede são de grande valia para o bom funcionamento do sistema. 7,10 A busca para ampliação estrutural é de extrema importância para conseguir atender toda demanda da região, ampliar o acesso adequado ao pré-natal e melhorar a atenção terciária em toda a Rede, por meio de intervenções específicas e de adequação ao que é preconizado, impactando, assim, de forma positiva no município de Anápolis e em todos os outros municípios da macrorregião.…”
Section: Conclusãounclassified